Neonatal diabetes - The role of KCNJ11 (Kir6.2) - Tammaro, P (2007)
ATP-sensitive potassium (KATP) channels are inhibited by intracellular ATP and activated by MgADP. As a consequence, they couple the metabolic state of the cell to its electrical activity. In pancreatic β-cells KATP channels regulate glucose-dependent insulin secretion and are the target for sulphonylurea drugs clinically employed in the treatment of type 2 diabetes. This review discusses recent advances in our understanding of the role of KATP channels in permanent neonatal diabetes mellitus. Copyright © 2007 S. Karger AG.